Analysis of Regional Difference and Correlation between Highway Traffic Development and Economic Development in China. Issue 3 (December 2018) - Li, Ye; Fan, Jing; Deng, Haopeng
This study used three-tier architecture to analyze the relationship between the highway traffic development difference and the economic development difference in China from 1997 to 2015. Their time distribution and trends of national and regional differences were quantified via both coefficient of variation and Theil index. Furthermore, the highway traffic connectivity was analyzed for each province. The obtained results showed that the difference of highway traffic development was significantly related to the difference of economic development, and poor connectivity of highway traffic was also strongly related to economic disparity. The investment difference of China's highway infrastructure could be divided into an unstable stage (1997–2010), and a stable stage (2011–2015). The highway traffic development difference could also be divided into two stages (1997–2006 and 2007–2015). Following the construction of central and western regions in around 2006, this difference decreased significantly; however, large differences within region remained. Provinces in the central and western regions have low connectivity and several remote main cities are not connected via high-grade highways. China's national economic difference has been constantly decreasing; however, the three regions follow different trends. Furthermore, with the development of the central and western regions, between-region economic differences decreased rapidly. To improve the level of regional equalization for highway development, the government should reduce differences between developed and undeveloped provinces for each region and connect remote cities, thus ultimately reducing differences in economic development and promoting a balanced regional development.